Two Dimensional Coherent Spectroscopy of CdSe/ZnS Colloidal Quantum Dots at Cryogenic Temperatures - Sun, B.; Almeida, D. B.; Singh, R.; Diederich, G. M.; Cundiff, S. T.; Padilha, L. A.; Bae, W. K.; Pietryga, J. M.; Klimov, V. I.; Siemens, M. E. (2015 CONFERENCE ON LASERS AND ELECTRO-OPTICS (CLEO), 2015)
We demonstrate 2D coherent spectroscopy of CdSe/ZnS nanocrystals and measure the exciton homogeneous linewidth as a function of temperature from 10K to 300K. The specra reveal contributions to the linewidth from discrete acoustic phonon modes. (C) 2014 Optical Society of America